ANALISIS PENGARUH SUHU DAN TEKANAN UDARA TERHADAP DAYA ANGKAT PESAWAT DI BANDARA SAM RATULANGI MANADO PERIODE 2010-2019 MENGUNAKAN METODE KORELASI PEARSON PRODUCT MOMENT - Kevin C. Emor; Rolles Nixon Palilingan; Donny Royke Wenas (Jurnal FisTa : Fisika dan Terapannya, 2021)
Temperature and air pressure are two elements of meteorology that are interrelated because air pressure together with temperature will determine the air density and will then determine the lift of an airplane. One of the disturbances that affect flight operations (lift) is temperature and air pressure. Research has been carried out, namely to determine the effect of air pressure and air temperature on flight operations (lift). Pearson Product Moment Correlation Analysis Method is a method used to determine how much the value of the relationship between temperature and air pressure on flight operations (lift) .From the results of research at Sam Ratulangi airport in Manado, it shows that the relationship between temperature and air pressure is very strong on flight operations in particular (Lift) on the airplane. By using data on F - Klim 71 in 2010 - 2019 the strongest relationship occurred in November and December with the determining coefficient values ​​of 97.29% and 99.91. Air pressure and air temperature together have a strong influence on flight operations specifically "lift". Meanwhile, air temperature tends to have a stronger influence on flight operations (lift) than air pressure.